(untitled) (Research, Society and Development, 2025)
Drug interaction consists of the modification, increase or decrease in the effect of a drug when administered concomitantly with another drug, which generates a different outcome than when only one of the drugs is administered. The objective of this study was to investigate the potential interactions between drugs used in the treatment of diabetes mellitus concomitantly with the treatment of arterial hypertension based on the literature. In this study, a literature review was carried out, with an in-depth search in several electronic databases LILASC, SCIELO and PUBMED considering publications between the years 2014 to 2024. The study was carried out using words that relate to the topic addressed, with the descriptors “Drug interactions”, “Drug interactions”, “Interactions between antihypertensives and antidiabetics”, “Antihypertensives and antidiabetics”. After analyzing 10 articles, the main interactions of the following drugs were found: Atenolol, Captopril, Spironolactone, Furosemide, Gliclazide, Glibenclamide, Hydrochlorothiazide, Insulin, Losartan, Metformin, Metoprolol Succinate and Valsartan. Some interactions show possible complications such as loss of glycemic and blood pressure control, and may also lead to renal failure. The concomitant use of medications for diabetes and hypertension requires care and attention from health professionals in order to avoid possible complications for patients.